(untitled) (REMUNOM, 2026)
Educational gamification has been identified as a promising strategy for fostering student motivation and engagement, particularly when aligned with clear pedagogical objectives and supported by effective teacher mediation. Among recent initiatives, digital gamification platforms can assist teachers in implementing gamified practices in schools, reducing the complexity involved in designing systems, rules, and monitoring dynamics. In this context, this article analyzes Classcraft as an educational gamification platform, describing its functioning and discussing its potentialities and challenges as a tool to support teaching practice. This study adopts a theoretical-reflective approach, based on the conceptual analysis of the platform and on dialogue with scientific literature on gamification, motivation, engagement, and academic emotions. The discussion indicates that features such as narrative elements, character customization, missions, immediate feedback, and cooperation may foster different dimensions of engagement and contribute to the organization of pedagogical work. However, it is emphasized that the effects of gamification are not automatic and depend on pedagogical intentionality, curriculum integration, and careful planning to avoid excessive reliance on extrinsic motivation. It is concluded that Classcraft can act as a mediator of teaching practice in the implementation of gamification, provided it is used critically, contextually, and in alignment with educational objectives.